Building Community Trust and Participation Through Transparency, Accountability, and Mosque Fund Governance: Empirical Evidence - Bagu, Agustin; Philep Njonjie; Nur Insani (Universitas Gorontalo, 2026)
This study aims to analyze the effect of transparency and accountability of mosque funds on community trust and participation, as well as to examine the role of governance as a moderating variable in mosques in Gorontalo City. This study employs a quantitative approach with a survey research design and is analyzed using Structural Equation Modeling (SEM) based on WarpPLS. The results of this study indicate that transparency can enhance community trust and participation. Accountability can enhance community trust and participation. Governance strengthens the relationship between transparency and community trust and participation. Governance also strengthens the relationship between accountability and community trust and participation.